High-resolution ultramicroscopy of the developing and adult nervous system in optically cleared Drosophila melanogaster. Issue 1 (December 2018) - Pende, Marko; Becker, Klaus; Wanis, Martina; Saghafi, Saiedeh; Kaur, Rashmit; Hahn, Christian; Pende, Nika; Foroughipour, Massih; Hummel, Thomas; Dodt, Hans-Ulrich
Abstract The fruit fly, Drosophila melanogaster, is an important experimental model to address central questions in neuroscience at an organismic level. However, imaging of neural circuits in intact fruit flies is limited due to structural properties of the cuticle. Here we present a novel approach combining tissue clearing, ultramicroscopy, and data analysis that enables the visualisation of neuronal networks with single-cell resolution from the larval stage up to the adultDrosophila . FlyClear, the signal preserving clearing technique we developed, stabilises tissue integrity and fluorescence signal intensity for over a month and efficiently removes the overall pigmentation. An aspheric ultramicroscope set-up utilising an improved light-sheet generator allows us to visualise long-range connections of peripheral sensory and central neurons in the visual and olfactory system. High-resolution 3D reconstructions with isotropic resolution from entire GFP-expressing flies are obtained by applying image fusion from orthogonal directions. This methodological integration of novel chemical, optical, and computational techniques allows a major advance in the analysis of global neural circuit organisation. Optical aberrations due to pigments in the eye and cuticle have undermined the ability for high-resolution imaging of the intactDrosophila . Here, the authors report an improved tissue-clearing agent, light-sheet optics and a multi-view combining algorithm to overcome these limitations.